2001
DOI: 10.1046/j.1526-4610.2001.041006559.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Daily Headache in the Posttrauma Syndrome: Relation to Extent of Head Injury

Abstract: This study suggests that the risk of developing posttraumatic chronic daily headache is greater for less severe head injury compared with moderate/severe head injury. The reason for this relation is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 23 publications
5
88
5
Order By: Relevance
“…However, the presence of CT scan abnormalities would classify these injuries in the moderate-to-severe category in some classification systems (Malec et al, 2007), making this sample more homogeneous and possibly limiting the extent to which differences in PTH incidence differ between injury severity classes. Prior research that has supported the idea of higher rates of headache in individuals with mild TBI has often focused on individuals presenting to outpatient clinics with a wide variation in time since injury and with varying presenting problems (Couch and Bearss, 2001;Uomoto and Esselman, 1993). While our mild group is likely more severely injured than those with mild TBI referred to in the literature, our rates of PTH with varying levels of severity of brain injury are similar and high.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of CT scan abnormalities would classify these injuries in the moderate-to-severe category in some classification systems (Malec et al, 2007), making this sample more homogeneous and possibly limiting the extent to which differences in PTH incidence differ between injury severity classes. Prior research that has supported the idea of higher rates of headache in individuals with mild TBI has often focused on individuals presenting to outpatient clinics with a wide variation in time since injury and with varying presenting problems (Couch and Bearss, 2001;Uomoto and Esselman, 1993). While our mild group is likely more severely injured than those with mild TBI referred to in the literature, our rates of PTH with varying levels of severity of brain injury are similar and high.…”
Section: Figmentioning
confidence: 99%
“…Headache was the only physical symptom that remained related to mild TBI after controlling for mental disorders (Hoge et al, 2008). Some studies have reported that the prevalence of PTH in civilian injuries is higher following mild TBI than moderate to severe TBI (Couch and Bearss, 2001;Lahz and Bryant, 1996;Uomoto and Esselman, 1993;Yamaguchi, 1992). Despite its high prevalence and chronicity, the actual diagnosis of PTH and its impact on functioning remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA that commences within 14 days of consciousness following TBI is termed posttraumatic HA (PTHA) [115]. Some investigations show higher prevalence of PTHA in milder TBI [111,[116][117][118], but this finding remains controversial given sample selection bias concerns and conflicting reports [119][120]. PTHA is usually self-limited but may become chronic.…”
Section: Headaches and Painmentioning
confidence: 99%
“…The presence of posttraumatic headache has not been consistently correlated with the severity of the injury; in fact, some authors have reported that mild TBI patients have higher rates of headache during the initial posttraumatic phase than patients with more severe injury. 37 In the majority of mild TBI cases, headaches resolve within 3 to 6 months. 38 Dizziness/Nausea Dizziness is the second most commonly reported somatic symptom of postconcussion syndrome.…”
Section: Somatic Symptoms Headachementioning
confidence: 99%